Continuous weaving $g$-frames in Hilbert $C^{*}$-modules (Jurnal Matematika, Statistika dan Komputasi, 2023)
The present paper aims to study $c$-$g$-woven for Hilbert $C^ {*} $-module spaces, first, we give some definitions and fundamental properties which will be useful to introduce the notion. And also some of his properties are given. Finally, we discuss the perturbation for $c$-$g$-woven.
Keywords: Continuous woven $g$-frames; $g$-frames; Hilbert $C^{*}$-module